2022
DOI: 10.3390/biomedicines10071559
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-138-5p Targets Pro-Apoptotic Factors and Favors Neural Cell Survival: Analysis in the Injured Spinal Cord

Abstract: The central nervous system microRNA miR-138-5p has attracted much attention in cancer research because it inhibits pro-apoptotic genes including CASP3. We hypothesize that miR-138-5p downregulation after SCI leads to overexpression of pro-apoptotic genes, sensitizing neural cells to noxious stimuli. This study aimed to identify miR-138-5p targets among pro-apoptotic genes overexpressed following SCI and to confirm that miR-138-5p modulates cell death in neural cells. Gene expression and histological analyses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 93 publications
(147 reference statements)
3
17
0
Order By: Relevance
“…Similarly, miR-138-5p which is involved in migration, axonal growth or in determining the size of dendritic spines [Kisliouk and Meiri, 2013; Liu et al ., 2013; Bicker et al ., 2014], has been shown to regulate both the expression and activity of pro-apoptotic factors (i.e. Casp3, Casp7 and Bak1) following traumatic spinal cord injury [Maza et al ., 2022]. This microRNA is upregulated during CNS maturation as observed previously in cortical development [Liu et al ., 2013].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, miR-138-5p which is involved in migration, axonal growth or in determining the size of dendritic spines [Kisliouk and Meiri, 2013; Liu et al ., 2013; Bicker et al ., 2014], has been shown to regulate both the expression and activity of pro-apoptotic factors (i.e. Casp3, Casp7 and Bak1) following traumatic spinal cord injury [Maza et al ., 2022]. This microRNA is upregulated during CNS maturation as observed previously in cortical development [Liu et al ., 2013].…”
Section: Discussionmentioning
confidence: 99%
“…1101 Post-transcriptional regulation by microRNAs has been described among many modulators of apoptotic effectors (such as caspases) during the maturation of neuronal cells. Several microRNAs target the Casp3 gene (coding for caspase-3 or CASP-3 protein) and control its expression, such as miR-138-5p [Park et al, 2018;Maza et al, 2022]. This microRNA is one of the most enriched in the CNS [Obernosterer et al, 2006;Ludwig et al, 2016], mainly expressed in both brain and spinal cord neurons and varying depending on neuronal subtype [Maza et al, 2022].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The miRNAs are short (19-25 nt) non-coding RNA sequences, involved in the regulation of cell physiological and pathophysiological mechanisms, including cell proliferation or death [26][27][28][29][30][31][32]. Studies from our group and other laboratories have shown the dysregulation of miRNA expression following traumatic SCI including those that regulate programmed cell death proteins [33][34][35]. The incremented miR-711 expression after SCI is associated with downregulation of the pro-survival protein Akt [36], whereas decreases in miR-27a may facilitate programmed cell death by allowing expression of pro-apoptotic Bcl-2 family proteins such as Noxa, Puma, and Bax [37].…”
Section: Introductionmentioning
confidence: 99%